DIAGNOSTIC ACCURACY OF COLOR FLOW DOPPLER IN THYROID TUMORS: Diagnostic Accuracy in Thyroid Tumors - Butt, Mah Gul Mumtaz; Nafees, Muhammad; Aquil, Hafsa (Pakistan Armed Forces Medical Journal, 2017)
Objective: To determine the diagnostic accuracy of color flow Doppler in differentiating between benign and malignant thyroid nodules and using FNAC as gold standard. Study Design: Validation study. Place and Duration of Study: Radiology Department, Benazir Bhutto and Allied hospital Rawalpindi for a period of six months, from Mar 2013 to Sep 2013. Material and Methods: The validation study was done at Radiology department, Benazir Bhutto and Allied Hospitals, Rawalpindi for the period of six months from 13th March to 13th September 2013. A total of 130 patients presenting with thyroid swelling with at least one dominant nodule, belonging to either sex were included through non probability consecutive sampling. Results: Sensitivity, specificity, positive and negative predictive values as well as accuracy of color flow Doppler ultrasonography in detection of malignant thyroid nodule was 93.3%, 97.4%, 82.4%, 99.1% and 96.9% respectively. Area under the curve (AUC) was 0.935 (p=0.0001). Conclusion: Color flow Doppler was found to be a useful diagnostic modality in the management of thyroid nodules, although the primary means should be FNA Biopsy.